Classification and types of risk for properties belonging to low-income and poor individuals in Malaysia - Mohd Fauzi, Puteri Nur Farah Naadia; Laldin, Mohamad Akram (EDP Sciences, 2019)
In Islam, the presence of risk is not only acknowledged but steps need to be taken to manage it properly through the process of risk management. One of the processes is the identification of risk which involves classification and types of risk. Specifically, in the development of properties, the presence of risks is inevitable. Improper management of risk especially for properties belonging to the low-income and poor individuals could mean that they will suffer from a bigger loss and poverty. Existing literature has shown and identified the inherent risks in the development of properties in Malaysia. However, risks exposed to in the development of properties belonging to the low-income and poor individuals in Malaysia are not properly identified. Consequently, a study is conducted to identify risks exposed to in the development of properties belonging to low-income and poor individuals in Malaysia. This study combines literature review and interview with experts and practitioners from various fields such as mua’malat, risk management, construction, developers, Majlis Agama Islam Negeri-Negeri (MAINs) and contractors. Findings from this study suggested that i) 94 risks were identified related to the development of properties belonging to low-income and poor individuals in Malaysia, and ii) Shariah elements i.e mua’malat and its requirements are included as one of the risks in the development of properties belonging to low-income and poor individuals in Malaysia. The findings become the basis and considered significant in assisting authorities and related organizations to understand and address risks accordingly and may assist the future development of a comprehensive Shariah compliance risk management for the development of properties in Malaysia.